Maximising the relevance and dissemination of the IOC medical consensus statements: key stakeholder`s perceptions of the IOC medical consensus statements in a developed country (Australia) - Badenhorst, M.; Fortington, L.; Bolling, C.; Pasanen, K.; Derman, W.; Verhagen, E.; Schwellnus, M.; Emery, C.; Finch, C. (British Journal of Sports Medicine, 2021)
Background :The IOC Medical and Scientific commission's mission is to provide a guiding reference for sports organisations on issues relating to the protection of the health of athletes. One strategy to achieve this mission is through supporting the development of consensus statements. Objective: This study investigates the relevance and dissemination of the IOC consensus statements among sports medicine professionals directly involved in Olympic athlete health in a developed setting (Australia). Design: Qualitative case study. Methods Semi-structured interviews, document analysis and field notes were utilised. Seven sports medicine professionals were interviewed. Results: For clinicians (not active in an academic/research setting), knowledge of the statements was limited; invitation to the study was the first awareness of the statements. Participants in leadership roles (with an academic/research component) were generally more familiar with some, but not all, statements. Participants identified a wealth of competing information sources through professional networks in health and sport. Subsequently, participants tend to consider these other avenues as first access point for information. Where statements were identified and used, there were several benefits reported, particularly drawn from the perceived leadership, trust, brand and reach of the IOC. While there is no formal adoption process for the information contained within a consensus statement, where identified as relevant, the information is shared amongst peer networks, via email or face-to-face meetings/seminars. There was agreement that the IOC has a role in the development and dissemination of the statements. However, interviewees also stated that information that is current and tailored to the target audiences (clinicians, coaches or athletes) could enhance the IOC's objective of guiding reference on athlete health. Conclusions A wealth of information is available to sports medicine professionals in Australia. Therefore, to enhance relevance and dissemination in a developed country, the IOC consensus statements must remain current and be tailored to target audiences.